Efforts to Improve Upper Passing Skills in Volleyball Games Through Media Targeting Ban on Students X IPA 2 SMA Negeri 4 Gowa - Benny Badaru; Sufitriyono Sufitriyono; Juhanis Juhanis; Retno Farhana Nurulita (UNIVERSITAS NEGERI MAKASSAR, 2023)
This research is a class action research (action research). This study aims to determine the increase in upper passing skills in volleyball game Target Tire Media in Students X IPA 2 SMA Negeri 4 Gowa. The subjects in this study were class X IPA 2 with a total of 37 students who would be given action in the form of target tire media on learning outcomes of upper passing in volleyball games. This study uses a class action research method, which consists of two cycles. Before the action was taken in cycle I the researcher gave an initial test to find out where the difficulties were in passing volleyball lessons, then learning is carried out using target tire media and ends with giving cycle I tests and cycle II tests with research instruments observation sheet tests of learning outcomes passing on volleyball using portfolio sheets. After the data was collected and analyzed, the results of the analysis were obtained: (1) From the data from the results of the Cycle I learning test, 20 people (54.05%) had reached the level of learning completeness, while 17 people (45.96%) had not reached the level of completeness. Study. With an average score of student learning outcomes is 64.4. (2) From the Cycle II learning achievement test, 30 people (81.08%) had reached the learning completeness level, while 7 people (18.91%) had not reached the learning mastery level, with an average score of 78 student learning outcomes. ,1. In this case it can be seen that there was an increase in the average value of student learning outcomes from cycle I to cycle II, namely an increase in classical completeness by 25%. Based on the results of data analysis, it can be said that through the media target tires can improve learning outcomes of upper passing in volleyball games in Students X IPA 2 SMA Negeri 4 Gowa.